A model based approach for the analysis and simulation of a hybrid bus in an urban context. Issue 3 (2018) - Gruosso, Giambattista; Bascetta, Luca
In recent years, environmental protection has become a goal shared by policy-makers, governments, private companies, and citizens. The large number of policies, such as the plan 20-20-20, and companies seeking to reduce emissions and energy consumption confirm this growing interest. Energy management becomes even more important in hybrid electric vehicles, to reduce pollutant emissions and minimise fuel consumption. Moreover, hybrid technology applied to urban transport increases in recent years, due to introduction of urban legislations including restricted traffic zones in city centres or restrictions on engine emissions. This paper aims at implementing a control strategy allowing to partialise energy sources that guarantees propulsion and operation of vehicle's auxiliary systems. A numerical model realised in Simulink is presented, taking into account all elements required to reproduce the behaviour of a Hybrid Bus. The control has been realised using if-then rules, considering the dynamic of every single component of the vehicle.